Policy Implementation Of Online Population Administration Services During The Covid-19 Pandemic In Lebak Regency, Banten, Indonesia - Nurhayati Nufus; Entang Adhy Muhtar; Budiman Rusli; Ramadhan Pancasilawan (Universitas Padjadjaran, 2022)
Population Administration Services continue to develop along with changes in people's lifestyles and technological developments. During the Covid-19 pandemic, the government began to focus on moving to the digital realm. The Banten Provincial Government, especially the Regency and City Population and Civil Registration Offices, has adapted to the development of Population Administration Services. Population Administration services are carried out in both cities and districts. Like one of them in Lebak Regency, services that were previously manual were pushed to be online during the pandemic. This article will discuss in more detail the implementation of Population Administration Services in Lebak Banten Regency, Indonesia, during the Covid-19 Pandemic and the differences before and after the pandemic. This study uses a descriptive qualitative approach. In collecting data, this research uses observation, interviews, literature study, and internet searching. Data collection in this study was carried out by studying the existing laws, regulations, and literature. We use Mazmanian and Sabatier (1983) implementation policy theory, namely the characteristics of the problem, the characteristics of the policy, and the policy environment. The findings of this article are that population administration services in Lebak Regency, Banten Province before Covid were still manual, even though there were already rules governing changes to digital. However, due to the pandemic, the system has changed to online and can be applied in many areas except with special conditions, such as in Kanekes Village, Lebak Regency, Banten Indonesia, where the community has special regulations.